2011
DOI: 10.4018/jkm.2011040101
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Process and Organizational Performance in SMEs

Abstract: The benefits of knowledge management are recognized mainly for the large organization. Small and medium-sized enterprises (SMEs) can also achieve the real benefits of KM. This paper investigates the relationship between the KM process and the organizational performance of SMEs. The objective of this paper is to assess the KM process and its relationship to different components of organizational performance in small and medium enterprise application service providers in Thailand. A survey approach was used with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Similarly, in a study of Portuguese technology-based SMEs, Ferreira & Franco (2017) found out that intellectual capital has a mediating effect on the relationship between strategic alliances and organizational performance. The organizational performance of SMEs can also be brought through knowledge performance, which increases process performance and eventually customer satisfaction, reputation, and cost reduction (Supyuenyong & Swierczek, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a study of Portuguese technology-based SMEs, Ferreira & Franco (2017) found out that intellectual capital has a mediating effect on the relationship between strategic alliances and organizational performance. The organizational performance of SMEs can also be brought through knowledge performance, which increases process performance and eventually customer satisfaction, reputation, and cost reduction (Supyuenyong & Swierczek, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Many argue that SMEs are not scaled-down versions of larger organizations (Supyuenyong & Swierczek, 2011), and that practices that apply to large organizations cannot necessarily be applied directly to SMEs (Coyte, Ricceri, & Guthrie, 2012;Pett & Wolff, 2011). For example, dedicated functions such as human resources (HR) generally manage knowledge activities in large firms, and Rechberg and Syed (2014) argue that formal HR practices for recruitment, selection and development are critical for knowledge acquisition and retention.…”
Section: Introductionmentioning
confidence: 99%
“…Another crucial contribution of this study is that most of the knowledge management literature has been conducted in Western countries [77]. Such studies include Martinez-Conesa et al (2017) [78] in Spain, O'Connor and Kelly (2017) [4] in the United Kingdom, and Downes and Marchant (2016) [79] in Australia.…”
Section: Theoretical Contributionsmentioning
confidence: 99%